Reflexões de um acadêmico em licenciatura integrada: experiências, vivências e memórias na formação educacional - VASCONCELOS, Mauro Duarte de (2019)
Work Completion of Course (TCC) in question presents the reflections of academic Mauro Vasconcelos student of the course Degree Integrated Education in Science, Mathematics and Languages of the Federal University of Pará elencando its multiple experiences in contact with academic life and the application of knowledge produced in research and practical analysis, as well as their experiences and how he was personally touched as soon as this process reliving this intense life journey through his memories, that is, what the marked and eternalized in its history. In existing chapters, I redo my life path from first contact to education permeating through my study in primary and secondary levels in the regular system and the difficulties presented that serve as a basis for analysis to the present-day period. Added to this, my experiences cast in the academic context exposing the researches focused on the inclusion and the role of the teacher as well as the analysis of the teacher student relationship in the context of development and learning, still takes the opportunity to highlight my practical experience in talking stage. This is revisiting my past so that we can understand, in depth and full of experiences as a professional is formed by the union of the transferred knowledge and situations experienced throughout his life, intrinsic mode.